Zakat Disbursement Efficiency Based on Zakat Core Principles in Managing Zakat Funds in Baznas of West Nusa Tenggara Province - Lenap, Indria Puspitasari; Sasanti, Elin Erlina; Karim, Nina Karina; Sari, Nungki Kartika (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2020)
This research aims to analyze the efficiency of zakat fund management in terms of its disbursements, Local Government Budget Allocation, and time according to the Zakat Core Principles in BAZNAS office of West Nusa Tenggara Province. There have not been many kinds of research that use Zakat Core Principles to measure zakat distribution efficiency in Indonesia. Most of the prior researches used Data Envelopment Analysis (DEA) and Malmquist Productivity Index (MPI) to measure zakat distribution efficiency. The results of this research show that the Disbursement Efficiency in 2014 is considered efficient, for the years of 2015 and 2017 it is considered very efficient, while for 2016 it is only considered quite efficient. The results of Local Government Budget Allocation analysis show that the operational costs coming from APBD for 2016 are classified as efficient, while for the years 2014, 2015 and 2017 it is classified as inefficient. The results of Time Efficiency analysis show that the amount of consumptive zakat being disbursed is categorized as satisfactory because it was disbursed four times in one year, while the disbursement of productive zakat can be categorized as fast because it was done six times in a year.Penelitian ini bertujuan menganalisis efisiensi pengelolaan dana zakat dari segi penyaluran, alokasi APBD dan waktu berdasarkan Zakat Core Principles pada BAZNAS Provinsi Nusa Tenggara Barat. Selama ini penelitian yang merujuk pada Zakat Core Principles sebagai alat ukur efisiensi penyaluran zakat masih sedikit dilakukan di Indonesia yang sebagian besar menggunakan Data Envelopment Analysis (DEA) dan Malmquist Productivity Index (MPI). Hasil penelitian menunjukkan bahwa kinerja Disbursement Efficiency pada tahun 2014 efisien, untuk tahun 2015 dan 2017 sangat efisien. Sementara, pada tahun 2016 cukup efisien. Hasil alokasi APBD menunjukkan bahwa biaya operasional yang berasal dari dana APBD pada tahun 2016 memiliki kinerja efisien. Sebaliknya, pada tahun 2014, 2015, dan 2017 tidak efisien. Hasil Time Efficiency menunjukkan bahwa jumlah penyaluran zakat konsumtif dikategorikan baik (4 kali dalam setahun). Sementara, zakat produktif dapat dikategorikan cepat (6 kali dalam setahun).